The Optimization of Matrix Preparation Process and Performance Testing for Molten Carbonate Fuel Cell - Jian Cheng; Liejin Guo; Shisen Xu; Ruiyun Zhang (Journal of Chemistry)
A key component in the molten carbonate fuel cell (MCFC) is electrolyte matrix, which provides both ionic conduction and gas sealing. The aim of this work is to investigate the effects of selected operating conditions on the performance of the matrix preparation. Slurries were prepared to produce matrices by the technique of tape casting. The characteristics of the slurries and matrices were examined by laser particle size analyzer, scanning electron microscopy, and BET surface area analyzer. The testing results revealed that a slurry composition with 40 wt.% lithium aluminate was the optimal formulation to produce a good matrix with a pore size distribution of 0.1–0.4 μm and porosity of 50 vol.%. Coarse and fine LiAlO2 particles were added in the matrix slurry to enhance the mechanical strength. Several green sheets were heated and pressed to enhance the bulk density to get a dense matrix of MCFC. Finally, a single MCFC was assembled and tested. The testing results showed the matrix with 40% solid loading gave the maximum discharge current of 20 A at 0.56 V.